Influence of Handprint Culture Training on Compliance of Healthcare Workers with Hand Hygiene - Hala Fouad; Mona M. A. Halim; HebatAllah F. Algebaly; Nardeen A. Elmallakh (Interdisciplinary Perspectives on Infectious Diseases)
Objective. We aimed to study the effect of visual observation of bacterial growth from handprints on healthcare workers’ (HCWs) compliance with hand hygiene (HH). Settings. Medical and postoperative cardiac surgery units. Design. Prospective cohort study. Subject. The study included 40 HCWs. Intervention. Each HCW was interviewed on 3 separate occasions. The 1st interview was held to obtain a handprint culture before and after a session demonstrating the 7 steps of HH using alcohol-based hand rub, allowing comparison of results before and after HH. A 2nd interview was held 6 weeks later to obtain handprint culture after HH. A 3rd interview was held to obtain a handprint culture before HH. One month before implementation of handprint cultures and during the 12-week study period, monitoring of HCWs for compliance with HH was observed by 2 independent observers. Main Results. There was a significant improvement in HH compliance following handprint culture interview (p<0.001). The frequency of positive cultures, obtained from patients with suspected healthcare-associated infections, significantly declined (blood cultures: p=0.001; wound cultures: p = 0,003; sputum cultures: p=0.005). Conclusion. The visual message of handprint bacterial growth before and after HH seems an effective method to improve HH compliance.